Metodología para la logística de distribución del sector retail de alimentos congelados para una cadena de minimercados en Bogotá (2021)
The objective of this article is to formulate a methodology for distribution logistics in the retail sector in order to create value, reduce costs, optimize time and generate customer and end consumer satisfaction. The model used for the development of the analysis of the methodology for distribution logistics has been the centralized model because its main base is the planning of routes allowing to evaluate different routes taking into account three main factors that affect logistics, these are described in the transfer of products to the points of sale, the distances to travel and the amount of product to be transported, to calculate the proximity of the exit point to the different mini markets a load-distance method is used, which led to the planning of costs for the implementation of the proposal.